Survei Tingkat Aktivitas Fisik Masyarakat Pasca Pandemi di Lapangan Mataram Kecamatan Pekalongan Barat - Amin, Ahmad Naufal; Darmawan, Agus (Indonesian Journal for Physical Education and Sport, 2023)
After the pandemic caused a decrease in public awareness in carrying out physical activities and the lack of public awareness of the importance of maintaining health and body immunity after the current pandemic, busyness made people neglect to do physical activity. West Pekalongan District. This type of research is descriptive with a quantitative approach using survey methods, with a population of people who use Mataram field as a center for physical activity in West Pekalongan District. The data collection technique used the short version of the IPAQ questionnaire from WHO. Data analysis techniques with continuous scores and norm scales were processed with SPSS 22 and Excel 2019. The results showed that the level of physical activity of the people in the Mataram Pekalongan Barat Field after the pandemic was 24 respondents (22%) doing high-intensity physical activity, while 47 respondents (43%) doing moderate physical activity, and 39 people doing low-intensity physical activity. respondents (35%) and the average respondent spent 275 minutes sitting a day or about 4.5 hours per day during weekdays. The conclusion from this study is that the level of physical activity of the community in Mataram Field, West Pekalongan District, is the most dominant medium intensity, namely 47 people (43%) after the pandemic. With community sitting activities an average of about 4.5 hours.